Activated AMP-activated protein kinase prevents hepatic steatosis, oxidative stress and inflammation in primary chicken hepatocytes - Yao, Yao; Li, Longlong; Wang, Huihui; Yang, Ying; Ma, Haitian (Frontiers in Physiology, 2022)
Fatty liver hemorrhagic syndrome (FLHS) in laying hens, a nutritional metabolic disorder disease, can lead to the decline of laying rate, shortening of laying peak period and increase of mortality, which seriously constrain the sustainable development of layer industry. Until now, there is no effective strategies can prevent and control the occurrence of FLHS in laying hens. The AMP-activated protein kinase (AMPK), a major sensor of cellular energy status, acts a crucial role in regulating lipid metabolism, oxidative stress and inflammatory responses in body. However, the potential molecular mechanisms about AMPK signal in controlling the occurrence of FLHS are remain unclear. In present study, we found that the phosphorylated AMPK (Thr172) protein level was markedly reduced in palmitic acid plus oleic acid (PO)-induced primary chicken hepatocytes. Moreover, blocked AMPK signal by AMPK inhibitor compound C obviously exacerbated lipid metabolism disorders, oxidative stress and inflammatory response triggered by PO in primary chicken hepatocytes. Nevertheless, the lipid metabolism disorders, oxidative stress and inflammatory response challenged by PO were obviously alleviated through activation of AMPK signal with AMPK activator AICAR in hepatocytes. In addition, we found that the beneficial effects of AMPK signal in relieving lipid metabolism disorders, oxidative stress and inflammatory response are achieved by activating the nuclear factor erythroid 2-related factor 2 (NRF-2)/kelch-like ECH-associated protein 1 (KEAP1) pathway and inhibiting the NF-κB pathway in PO-stimulated primary chicken hepatocytes. Collectively, our data demonstrated that AMPK acts as a potential target for the prevention of FLHS occurrence in laying hens.